Advances in the Diagnosis and Treatment of Insertional Achilles Tendinopathy: A Comprehensive Review - Yang, Weijie; Zan, Qiang (Journal of Contemporary Medical Practice, 2025)
Insertional Achilles tendinopathy is a chronic condition characterized primarily by degenerative changes at the insertion site of the Achilles tendon. It commonly affects athletes and middle-aged individuals, with typical clinical manifestations including pain at the posterosuperior aspect of the heel, morning stiffness, and start-up pain. Although various treatment methods are available, there is no unified standard of care, and the efficacy of each approach varies considerably. This review comprehensively examines the anatomy and pathological changes of the Achilles tendon, as well as the diagnosis and treatment of insertional Achilles tendinopathy, with a particular emphasis on therapeutic strategies, aiming to provide insights for clinical management.